Efficacy Study of Learning Management for Developing International Folk Dance Skills in the Subject of Rhythmic Activities Using the Davies' Practical Skills Teaching Method for Secondary School Third-year Students - Pooboonim, Watcharin (International journal of education and literacy studies, 2025)
The aims of this research are: 1) to determine the effectiveness of learning management in developing international folk dance skills in the course of Rhythmic Activities, using the Davies' practical skills teaching method for secondary school third-year students according to the 80/80 criteria; 2) to compare international folk dance skills after being taught by using the Davies' Practical Skills teaching method between, before and after studying, which the passing criteria of the post-test was set at 75 percent; 3) to study the satisfaction of secondary school third-year students after receiving learning management in the subject of rhythmic activities by using the Davies' Practical Skills teaching method for the sample group. The sample group used was 43 students of the third-year secondary school at Mahasarakham University Demonstration School (Secondary), Semester 1, in the academic year 2024.  The research tools were 1) the learning management plan for international folk-dance practice skills of the third-year students.  The plan included 5 plans, which was 10 hours in total. The plan’s evaluation result was at the most appropriate level ( = 4.79). 2) the 30 item, 4 alternative pre-test and post-test which was used to measure international folk-dance practice skills before and after the activity. The test had a difficulty value between 0.05-0.89 with the discrimination value between 0.23-0.74 and the reliability value of 0.85-. 3 while the questionnaire had a discrimination value of between 0.44 and 0.81 and a reliability value of 0.94.  Statistics used in the data analysis were percentage values (percentage), mean ( ), standard deviation (SD), and a statistics T-test. The research results revealed that: 1) Learning management in developing international folk-dance skills in the course of Rhythmic Activities using the Davies' Practical Skills teaching method for secondary school third-year students was equally effective at 95.81/87.05.  This result meets the specified criteria of 80/80; 2) Students gained international folk-dance skills after being taught using the Davies' Practical Skills. The criteria were 75 percent higher after studying than before studying. This result was statistically significant at the .05 level; 3) Secondary school third-year students, after receiving learning management in the rhythmic activity course using the Davies' Practical Skills teaching method to develop international folk-dance skills reached a highest level of satisfaction with an average of (  = 4.51 and SD = 0.19).